The Impact of Statins on FGF–2—Stimulated Human Umbilical Vein Endothelial Cells. Issue 1 (January 2014) - Burgazli, Kamil Mehmet; Behrendt, Mark Andre; Mericliler, Meric; Chasan, Ritvan; Parahuleva, Mariana; Erdogan, Ali
Abstract: Aim: To determine the effects of different types of statins on proliferative and migrative behaviors of basic fibroblastic growth factor (FGF)–2–stimulated endothelial cells.Materials and Methods: Human umbilical vein endothelial cells (HUVECs) were isolated and cultured. Groups were arranged in order to observe the impact of each individual substance alone, or under stimulation with statin on FGF–2–stimulated endothelial cells. Endothelial cells were stimulated with human growth factor (HGF), statins, methyl–β–cyclodextrin (β–MCD), and either farnesyl pyrophosphate (FPP) ammonium salt, or geranylgeranyl–pyrophosphate (GGPP), respectively. Cell proliferation analyses were performed 48 hours after stimulation and gaps between migration borders were used in migration analyses.Results: The statins showed significant antiproliferative and anti–migrative effects and inhibited the proliferative behavior of FGF–2. However, endothelial cell proliferation and migration were significantly increased after mevalonate co–incubation. Experiments with β–MCD indicated that the destruction of lipid rafts had a negative impact on the action of FGF–2. Stimulation of statin–incubated cells with FPP had no additional effect on proliferation or migration. Notably, although FGF–2 exerted a pro–migrative effect, the effect was not shown in the FPP + FGF–2 group. The anti–migrative actions of statins along with disruption of membrane integrity were reversed by the addition of GGPP.Conclusion: The angiogenic effect of FGF–2 is suppressed through inhibition of the intracellular cholesterol biosynthesis via statins. Inhibitory effects of statins on FGF–2—stimulated HUVECs were observed to result from both the inhibition of isoprenylation and the destruction of lipid rafts on the cell membrane.